Sekilas Tentang Kehidupan Masyarakat Etnis India Di Kota Medan - Haris Wijaya; Fauzia Agustini; Nurul Sabrina (Jurnal Pendidikan Ilmu Pengetahuan Sosial (JPIPS), 2021)
This research aims to know at a glance about the Indian community in Medan. This type of research is qualitative research. The research location in Medan city is mainly Madras Hulu area. Method of data collection is done through interviews, observation, literature studies and using a list of questions. Indonesian Ethnic Indian community who since birth has been in Medan city because it has interacted, and mingled with other citizens, the results of a brief study of ethnic Indian communities in Medan related to language, religion, occupation, and culture. For ethnic Indians who have been in Medan since birth, they use Bahasa Indonesia every day even they can not use Indian. The work that some ethnic Tamil Indians have is rough work like parking attendants and so on. In general, religions embraced by ethnic Indians in Medan are Hinduism, Buddhism, and Islam. The results of the interview of the three informants showed that although they were born in Medan, they still hold Indian Culture